Categorization Of Thrace Bektashi Melodies And Their Relations With Eurosia Environs (Journal of Alevism-Bektashism Studies, 2010)
Ethnomusicology- anthropology, which is effective in folk music studies and which has high financial power is a more powerful trend. Comparative study method which focuses on musical analysis has started to gain its power again. I tried to give an example for it in this article. This article is not about the social and cultural aspects of Bektashism. It is just a study of compara- tive analysis of their songs which is only a small part of their cultures. My primary aim is to show the basic melodies that can successfully represent most of the melodies. Another aim of mine is to make a comparison between the music of some peoples who have regional and historical ties with Bektashis. I hope that this ar- ticle will help to better understand the secular and mystical music of Thrace Bektashis, and to place this music among other music types.